Herbal medicine use in the Jordanian population: A nationally representative cross-sectional survey - Derar H. Abdel-Qader; Abdullah Albassam; Najlaa Saadi Ismael; Mohammed S. Aljamal; Li-Chia Chen; Kenza Mansoor; Salim Hamadi; Nadia Al Mazrouei; Ahmad Z. Al Meslamani (GarVal Editorial Ltda., 2020)
Context: Despite of potential adverse effects, the use of herbal medicines has grown globally without proper regulatory measures. There is a scarcity of data on the pattern of use and general awareness towards herbal products among the Jordanians. Aims: To assess the prevalence, utilization, and attitude toward herbal medicines among the Jordanian public. Methods: A national cross-sectional self-reported survey on a random sample of adult population aged ≥ 18 years was conducted over two months to include 1820 adults in Jordan. A representative sample was collected using a proportionate random sampling technique, which enabled us to categorize the study population geographically. SPSS V26 was used for data analysis. Results: The prevalence of herbal medicine use was 53.3% (971/1820), and respondents who aged >29 years were more likely to use herbal products. Predictors for using herbal products were: females (OR 4.23; 95%CI 1.97-9.55; p=0.0004), fair health status (OR 7.19; 95%CI 5.49-13.85; p=0.0001), and participants without chronic diseases were significantly less likely to use herbal medicines (OR 0.21; 95%CI 0.11-0.61; p=0.0007). The majority of respondents (86.5%, 1574/1820) thought herbal products were safe because they were made from natural ingredients. The most common reasons for using herbal products were chronic disease treatments (41.9%, 407/971), weight reduction (23.6%, 229/971), and to less extent improving the well-being (16.2%, 157/971). Conclusions: More than half of the targeted population used herbal medicines, a quarter of whom experienced adverse effects. The findings of this study have major community health implications for Jordan.